Can community media programmes serve as developmental approaches for at-risk youth? - Charles Rachel-Ann (Cultural Science)
This paper examines the Shoot to Live community media initiative and data collected from this study will provide a discussion on whether or not this programme can be used as a development approach for at-risk youth. Discourses on community media, youth and development will be used as the theoretical framework for this study. Accordingly, theory and practice from these constructs can be used to develop ideas that emerge from the Shoot to Live programme. This paper initially assesses some of the various degrees of success of this community media initiative. Finally, the findings of this study will play a pertinent role in the creation, evaluation and transformation of future community media programmes and youth development approaches particularly in developing countries.